2015
DOI: 10.1063/1.4938068
|View full text |Cite
|
Sign up to set email alerts
|

Examination of humidity effects on measured thickness and interfacial phenomena of exfoliated graphene on silicon dioxide via amplitude modulation atomic force microscopy

Abstract: The properties of Few-Layer Graphene (FLG) change with the number of layers and Amplitude Modulation (AM) Atomic Force Microscopy (AFM) is commonly used to determine the thickness of FLG. However, AFM measurements have been shown to be sensitive to environmental conditions such as relative humidity (RH). In the present study, AM-AFM is used to measure the thickness and loss tangent of exfoliated graphene on silicon dioxide (SiO2) as RH is increased from 10% to 80%. We show that the measured thickness of graphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 25 publications
2
8
0
Order By: Relevance
“…However, it has been found that water molecules diffuse to the interfaces between the single-layer materials and their underlying substrate in humid environments, which leads to the formation of ice-like water adlayers at these interfaces. The diffused water molecules were shown to increase the thickness and change the mechanical properties of these materials [39,40]. Given that friction in 2D materials is strongly influenced by mechanical properties and substrate interactions, the diffused water molecules could, in turn, also affect their frictional behaviors [41].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been found that water molecules diffuse to the interfaces between the single-layer materials and their underlying substrate in humid environments, which leads to the formation of ice-like water adlayers at these interfaces. The diffused water molecules were shown to increase the thickness and change the mechanical properties of these materials [39,40]. Given that friction in 2D materials is strongly influenced by mechanical properties and substrate interactions, the diffused water molecules could, in turn, also affect their frictional behaviors [41].…”
Section: Resultsmentioning
confidence: 99%
“…For example, bulk MoS 2 exhibited better tribological performance, including friction reduction and wear resistance, in vacuum and dry environments than in humid environments, whereas operating in vacuum and dry conditions resulted in significant degradation in tribological performance of graphite [37,38]. For single-layer materials, it has also been shown that water molecules can diffuse to the material-substrate interface and form an ‘ice-like’ water adlayer, resulting in an increase in thickness and change in mechanical properties [39,40]. Given that friction of 2D materials is strongly dependent on mechanical properties and their interactions with the underlying substrates, diffused water molecules could have significant impact on frictional behaviors of the materials.…”
Section: Introductionmentioning
confidence: 99%
“…The values of these loss tangents are in the same range as found by Jinkins et al . 45 . The obtained values for the loss tangent are relatively high for a bulk crystalline material, therefore the observed loss tangent is likely dominated by effects related to the atomic thickness of graphene, such as thermodynamic fluctuations 46 , sidewall adhesion 47 or unzipping of wrinkles 48 .…”
Section: Mechanical Loss Tangentmentioning
confidence: 99%
“…These values are compatible to 4–6 layers for FLG and 1–2 layers for GBD, in agreement with the results extracted from Raman spectroscopy. The measured thickness values take into account of the presence of water buffers between the stack and SiO 2 and between each layers of the stack . We measured the UV–vis absorption of FLG/GBD stack transferred onto quartz substrate and the result has been compared with the absorption of graphene (Figure c).…”
Section: Resultsmentioning
confidence: 99%
“…The measured thickness values take into account of the presence of water buffers between the stack and SiO 2 and between each layers of the stack. [66][67][68] We measured the UV-vis absorption of FLG/GBD stack transferred onto quartz substrate and the result has been compared with the absorption of graphene (Figure 2c). The absorption spectrum of the stack is dominated by a pronounced peak at %270 nm (4.6 eV).…”
Section: Structural Characterization Of Graphene and Gbd Layersmentioning
confidence: 99%